Building Sustainable Health Ecosystems 6th International Conference on Well-Being in the Information Society, WIS 2016, Tampere, Finland, September 16-18, 2016, Proceedings - Li, Hongxiu; Nykänen, Pirkko; Suomi, Reima; Wickramasinghe, Nilmini; Widén, Gunilla; Zhan, Ming (Communications in Computer and Information Science, 2016)
This book constitutes the refereed proceedings of the 6th International Conference on Well-Being in the Information Society, WIS 2016, held in Tampere, Finland, in September 2016. The 21 revised full papers presented were carefully reviewed and selected from 42 submissions. With the core topic "Building Sustainable Health Ecosystems" WIS 2016 focused on innovations and fresh ideas in the cross-section of urban living, information society and health as understood in a wide sense. The papers presented in this volume are organized along the following seven broad topics: 1. Macro level considerations of e-health and welfare, 2.Welfare issues of children, youth, young elderly and seniors, 3. Analytics issues of eHealth and welfare, 4. National/regional initiatives in eHealth and welfare, and 5. Specific topics of eHealth. The papers in these topics span qualitative and quantitative analysis, empirical surveys, case studies as well as conceptual work.